PSIKO SPIRITUAL ISLAM: SEBUAH KAJIAN KESEHATAN MENTAL DALAM TASAWUF - Khairunnas Rajab (Millah: Journal of Religious Studies, 2010)
Islamic values which are directly related to the human psyche. This study is more focused on mysticism, as in Sufism spiritual values with more coherent and intuitive approach similar to the dimensions of psychology. Sufic itself is an al-nafs tadzkiyyah method that can bring happiness, calmness and mental health.